2005
DOI: 10.1073/pnas.0502416102
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of DNA–anionic liposome complexes reveals hierarchy of ion-mediated interactions

Abstract: Self-assembled DNA delivery systems based on anionic lipids (ALs) complexed with DNA mediated by divalent cations have been recently introduced as an alternative to cationic lipid-DNA complexes because of their low cytotoxicity. We investigate AL-DNA complexes induced by different cations by using synchrotron small angle x-ray scattering and confocal microscopy to show how different ion-mediated interactions are expressed in the selfassembled structures and phase behavior of AL-DNA complexes. The governing int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 35 publications
4
70
0
Order By: Relevance
“…It is known that charged polymers can induce electrostatic wrapping by oppositely charged membranes (27)(28)(29), so cationic peptides (e.g., polyarginine and polylysine) naturally generate negative mean curvature via induced electrostatic wrapping of the peptide by anionic cell membranes. The guanidinium side group in arginines can form multidentate hydrogen bonds with the phosphates of lipid head groups and associate with multiple lipid molecules (22,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that charged polymers can induce electrostatic wrapping by oppositely charged membranes (27)(28)(29), so cationic peptides (e.g., polyarginine and polylysine) naturally generate negative mean curvature via induced electrostatic wrapping of the peptide by anionic cell membranes. The guanidinium side group in arginines can form multidentate hydrogen bonds with the phosphates of lipid head groups and associate with multiple lipid molecules (22,30,31).…”
Section: Resultsmentioning
confidence: 99%
“…In such systems the packing parameter, as defined by Israelachvili [184], predicts the formation of spherical vesicles, so it may not be surprising that most DNA nanoparticles have been described as spherical, ellipsoidal or globular [185,186]. However, significant reorganization of lipid vesicles is observed to occur, resulting in multilamellar organization of the lipids with alternating plasmid molecules oriented parallel to one another as a result of long-range electrostatic interactions [181,182,187]. This parallel orientation of plasmids gives rise to the characteristic fingerprint pattern often seen in electron microscopy micrographs of DNA nanoparticles (Figure 5).…”
Section: Nanoparticle Properties Important In Transfectionmentioning
confidence: 98%
“…Membrane charge density has become recognized as a universal parameter [180] that governs the transfection efficiencies in nanoparticles formed from a binary mixture of lipids (i.e., one cationic and one neutral helper lipid) [181,182]. When extended to multicomponent lipid systems, the transfection efficiency can be modeled as a function of membrane charge density fit to a Gaussian equation.…”
Section: Nanoparticle Properties Important In Transfectionmentioning
confidence: 99%
“…Anionic liposomal DNA delivery vectors as an alternative to cationic liposomes have been reported in recent years (11,12). Anionic lipids in general are less cytotoxic (13) and some of them are the endogenetic components of eukaryotic cell membranes (14). It was demonstrated that a novel anionic lipoplex DNA delivery system encoding a gene of interest resulted in high transfection efficiency, good serum stability and low toxicity in vitro (15).…”
Section: Introductionmentioning
confidence: 99%